The Influence of Good Corporate Governance and Corporate Social Responsibility on the Value of Banking Companies Listed on the Indonesia Stock Exchange - Anhar Firdaus Firdaus; Fazli Syam BZ; Yossi Diantimala Diantimala; Syawal Harianto Harianto (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2021)
This reasearch purpose to examine the Good Corporate Governance and Corporate Social Responsibility both simultaneously and partially to Firm Value on Indonesian Banks in the period of 2011-2015. The methode of analysis used in this reasearch is path analysis for hypotesting test and SPSS for classic assumption test. The type used in this reasearch is study are causality, using purposive sampling method and unbalanced panel data. The object of this reasearch consists of 11 banks with 38 observational data. The results show that (1) Good Corporate Governance and Corporate Social Responsibility simultaneously no influence to firm value; (2) Good Corporate Governance has no influence to firm value; (3) Corporate Social Responsibility has no influence to firm value.